EFFECT OF RUTHKOFF MODEL USING MASTERY LEARNING STYLE IN LEARNING SOME BASIC FOOTBALL SKILLS AMONG STUDENTS - Dahham, Nahidh Abboud (Universitas PGRI Yogyakarta, 2025)
Learning basic football skills requires effective teaching models that can foster engagement and improve performance outcomes. Traditional approaches often fail to maximize students’ potential, particularly in skill-based subjects that demand both repetition and mastery. This study aimed to investigate the effect of the Rothkopf model using the mastery learning style on the acquisition of basic football skills among students. The research employed an experimental method with two equivalent groups (experimental and control). The sample consisted of 124 fourth-grade secondary students from Al-Suwaira Preparatory School for Boys during the academic year 2024–2025, representing classes A, B, and C. Data were collected through pre- and post-tests of passing, ball control, and dribbling, and analyzed using the SPSS software package. The findings revealed that students in the experimental group, who received instruction based on the Rothkopf model with mastery learning, showed significantly greater improvements in all measured skills compared to the control group. These results indicate that the Rothkopf model with mastery learning not only enhances skill acquisition but also increases motivation and engagement in the learning process. The study concludes that this model provides an effective instructional framework for teaching football skills and recommends its broader application in physical education curricula. The main contribution of this research lies in demonstrating how structured instructional design, rooted in mastery learning principles, can optimize the teaching of sports skills and support student-centered learning outcomes.